Implementing MALL approach in teaching Indonesian imperatives to Korean learners: A case study - Nur Utami Sari'at Kurniati; Dong Hoon Kim (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2026)
The study examines the use of smartphone applications as a tool in teaching Indonesian to university students in South Korea. This case study specifically examines the implementation of the Mobile-Assisted Language Learning (MALL) approach in teaching Indonesian imperatives. This type of sentence does not contain complex affixes, and it is commonly used in everyday speech. The study involves 15 Korean learners, 11 females and four males, enrolled in the Elementary Indonesian class. They were freshmen, and none of them had ever resided in Indonesia. Data are collected through documentation from screen-recorded tutorial videos on using smartphone applications. There were 97 imperative sentences from 15 videos, which have an average duration of 1 minute and 12 seconds. The findings reveal that as many as 83.6% of the total number of imperatives in the videos are grammatically correct in terms of phonological, morphological, syntactical, and semantic aspects. The result on the pronunciation shows a simplification process in the pronunciation of Indonesian consonant clusters, sound changes, and neutralization. On the morphological level, there were some cases in which wrong forms of the verbs were used. The syntactical analysis indicates wrong phrase and sentence structure, in particular the second type of Indonesian passive sentence. The semantic level indicates that the incorrect word choice leads to the wrong meaning of the message.